Teacher Workload and Organizational Culture as Predictors of Turnover Intention among Junior High School Teachers - Kusuma Galih Ayusaputri; Laili Komariyah; Moh Bahzar (Borneo Research and Education Center, 2026)
Teacher turnover intention has become an important concern in educational institutions because it may affect instructional continuity and school effectiveness. Drawing on the Job Demands–Resources (JD-R) framework, this study examined the relationships between teacher workload, organizational culture, and turnover intention among public junior high school teachers in Indonesia. A quantitative cross-sectional survey was conducted involving 180 teachers from public junior high schools in Samarinda Ulu District, selected through proportionate random sampling. Data were collected using structured questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicated that teacher workload and organizational culture jointly explained 59.3% of the variance in turnover intention (R² = 0.593). Teacher workload was positively associated with turnover intention (β = 0.484, p < 0.001), whereas organizational culture was negatively associated with turnover intention (β = −0.332, p < 0.001). Workload demonstrated a stronger contribution to turnover intention than organizational culture. These findings suggest that both job demands and job resources are important factors associated with teachers’ intentions to remain in or leave their schools. The study contributes to the application of the JD-R framework in the context of Indonesian public junior high schools and highlights the importance of managing teacher workload while fostering a supportive organizational culture to strengthen teacher retention.